Kortikosteroid Oral Jangka Pendek sebagai Tata Laksana Psoriasis Vulgaris: Sebuah Laporan Kasus - Linus, Ariel; Moniaga, Catharina Sagita; Sutedja, Gina Triana (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: While oral corticosteroids are not included in the psoriasis systemic therapy algorithm, they are still utilized in certain cases because of their anti-inflammatory and immunosuppressive properties. This case report describes a case of psoriasis vulgaris treated with oral corticosteroids as replacement therapy for first-line drugs. Case Illustration: A 53-year-old male presented to Ciawi Regional Hospital with a complaint of a red, scaly rash that had been itchy on his back for a year, which was spreading to his entire body and worsening over the last 3 months. The physical examination revealed erythematous papules and plaques with thick, silver scales throughout his body. He was diagnosed with psoriasis vulgaris, with a Psoriasis Area Severity Index (PASI) score of 32.6. The patient utilized National Health Insurance, which did not cover the first-line drugs; therefore, he was prescribed oral methylprednisolone instead. After two weeks of medication, his clinical manifestations improved, resulting in a PASI score of 5.5. Discussion: The oral corticosteroid provided a significant improvement in skin lesions for this patient. This improvement may be due to its anti-inflammatory and immunosuppressive effects. Close monitoring after treatment is crucial, as flare-ups and side effects may occur after treatment with oral corticosteroids. Conclusion: The use of oral corticosteroids in the treatment of psoriasis vulgaris is an option when first-line drugs are not available, followed by post-treatment observation